Le plurilinguisme dans les cultures populaires, un terrain inexploré? L’étude du langage mixte du rap montréalais en guise d’exemple - Low, Bronwen (Kinephanos, 2012)

‘Ch'us mon propre Bescherelle’: Challenges from the Hip-Hop nation to the Quebec nation - Low, Bronwen; Sarkar, Mela; Winer, Lise (Journal of Sociolinguistics, 2009)
We examine the uses of and attitudes towards language of members of the Montreal Hip-Hop community in relation to Quebec language-in-education policies. These policies, implemented in the 1970s, have ensured that French has become the common public language of an ethnically diverse young adult population in Montreal. We argue, using Blommaert's (2005) model of orders of indexicality, that the dominant language hierarchy orders established by government policy have been both flattened and reordered by members of the Montreal Hip-Hop community, whose multilingual lyrics insist: (1) that while French is the lingua franca, it is a much more inclusive category which includes ‘Bad French,’ regional and class dialects, and European French; and (2) that all languages spoken by community members are valuable as linguistic resources for creativity and communication with multiple audiences. We draw from a database which includes interviews with and lyrics from rappers of Haitian, Latin-American, African-American and Québécois origin.
Keywords: Order of indexicalities; Quebec language policy; multilingual code-switching; normative tradition (French); rap lyrics; urban youth culture

"Pour connecter avec le peeps": Québéquicité and the Quebec Hip-Hop Community - Sarkar, Mela; Low, Bronwen; Winer, Lise (Identity and Second Language Learning: Culture, Inquiry, and Dialogic Activity in Educational Contexts, 2006)

Translanguaging in the Multilingual Montreal Hip-Hop Community: Everyday Poetics as Counter to the Myths of the Monolingual Classroom - Low, Bronwen; Sarkar, Mela (Heteroglossia as Practice and Pedagogy, 2014)
This chapter explores the possibilities multilingual hip-hop offers for language instruction within multiethnic classrooms in Montreal shaped by multiple discursive practices. The authors review current research on multilingualism and teaching and propose strategies for overcoming the French prescriptivist monolingual mindset in education in Quebec. They also turn to poetics, and in particular the literary theory of Edouard Glissant (Caribbean discourse, 1989; Poetics of relation, 1997) and the Martinican school of Créolité, offering possibilities for rethinking relationships between oral and written, vernacular and standard language forms and for igniting language teachers’ pedagogic imaginations.
Keywords: Creolization; Hip-hop; Oraliture; Popular culture

De- and Reterritorializing Identities: The Global Hip Hop Nation at Work in a Youth Hip Hop Recording Studio - Laniel-Tremblay, Édouard; Low, Bronwen (Critical Approaches Toward a Cosmopolitan Education, 2022)
This essay builds on previous studies of the “translanguaging” practices of members of the Montreal Hip Hop community (Low & Sarkar, 2014; Sarkar & Low, 2012) to explore how the challenge to linguistic norms in Quebec is also a challenge to social and identity norms. Our analysis is based on interviews with young musicians attending a community recording studio program in Montreal, the studio’s social media presence, and a track created in collaboration with youth in Paris. Through their relationships in the studio as well as their music, the youth de- and reterritorialize their identities (Papastergiadis, 2000), mobilizing local and global Hip Hop cultural references and communities in ways that challenge dominant narratives of belonging in Quebec and Canada.